It's kind of a funny story [videorecording (DVD)] - Fleck, Ryan, 1976-; Fleck, Ryan, 1976-; Boden, Anna; Boden, Anna; Gilchrist, Keir, 1992-; Graham, Lauren, 1967-; Galifianakis, Zach; Roberts, Emma, 1991-; Davis, Viola, 1965-; Gaffigan, Jim (Universal, 2011)
Sometimes what's in your head isn't as crazy as you think ... that's certainly true for Craig, a stressed-out teenager who checks himself into a mental health clinic for some time out. What he finds instead is an unlikely mentor, a potential new romance and an opportunity to begin anew. Charming, witty and smart, it's a coming-of-age story that's kind of a funny story.